10 commandments of smile esthetics - Machado,Andre Wilson (2014)
The search for esthetic treatment has persisted in the routine of dental professionals. Following this trend, dental patients have sought treatment with the primary aim of improving smile esthetics. The aim of this article is to present a protocol to assess patient's smile: The 10 Commandments of smile esthetics.